The Impact of Transformational Leadership Factors on Public Service Innovation Outcomes: An Evidence from Bangladesh - Shumshunnahar, Mst. (Advances in Social Sciences Research Journal, 2021)
The aim of this research is to examine the effect of the factors of Transformational leadership on public service innovation outcomes. Survey data collected from 500 innovation officers of field level administration of Bangladesh. Results from the multiple regression analysis using SPSS indicated that there was a positive impact of Idealized Influence, Inspirational Motivation, Intellectual Stimulation and Individualized Consideration on public service innovation outcomes. The finding also implies that the policy makers should build a strong strategy to put more concentration and heighten transformational leadership to enhance public service innovation outcomes.